Impact Of Pharmacist Homecare Service On Medication Adherence And Knowledge Among Hypertensive Patients In Seremban - Supian, Azuwana (2010)
Hypertension is one of the major public health problems in Malaysia due to its high prevalence (42.6% in 2006), lack of awareness amongst the general population, its poor control and its impact on cardiovascular morbidity and mortality. A common reason for inadequate control of hypertension is low adherence with antihypertensive medicine regimen. Therefore, this research was conducted to assess and evaluate patients’ adherence and to examine the impact of “Pharmacist Homecare Service (PHS)” provision on the patients’ adherence, blood pressure reduction and knowledge among hypertensive patients.